Sleep enhances explicit recollection in recognition memory - Drosopoulos, Spyridon (Cold Spring Harbor Laboratory Press, 2005)
Recognition memory is considered to be supported by two different memory processes, i.e., the explicit recollection of information about a previous event and an implicit process of recognition based on an acontextual sense of familiarity. Both types of memory supposedly rely on distinct memory systems. Sleep is known to enhance the consolidation of memories, with the different sleep stages affecting different types of memory. In the present study, we used the process-dissociation procedure to compare the effects of sleep on estimates of explicit (recollection) and implicit (familiarity) memory formation on a word-list discrimination task. Subjects studied two lists of words before a 3-h retention interval of sleep or wakefulness, and recognition was tested afterward. The retention intervals were positioned either in the early night when sleep is dominated by slow-wave sleep (SWS), or in the late night, when sleep is dominated by REM sleep. Sleep enhanced explicit recognition memory, as compared with wakefulness (P < 0.05), whereas familiarity was not affected by sleep. Moreover, explicit recognition was particularly enhanced after sleep in the early-night retention interval, and especially when the words were presented with the same contextual features as during learning, i.e., in the same font (P < 0.05). The data indicate that in a task that allows separating the contribution of explicit and implicit memory, sleep particularly supports explicit memory formation. The mechanism of this effect appears to be linked to SWS.